Strategi Guru dalam Meningkatkan Motivasi Belajar PAI pada Siswa Berkebutuhan Khusus - Yoga Sari Prabowo (Tarbiyah Departement collaboration with AMCA, 2015)
Motivation to learn is the power (power motivation) and the driving force (driving force), or tool builder willingness and strong desire for self-learners for active learning, creative, effective and innovative and enjoyable in a change of behavior in both the cognitive, affective and psychomotor. So that motivation to learn is possessed by the learners, the teachers are required expertise in determining appropriate strategies in learning so as to motivate the learners, both internally and externally. If learners are motivated to learn by itself will have an impact on the process and the expected learning outcomes and can be used as a basis to know ketercapian purpose of learning by learners.